Protocol for the practice guideline for traditional Chinese medicine preventive treatment on insomnia disorder - Duan, Yuting; Wang, Yu; Yang, Haichun; Cai, Yuejuan; Wu, Shengwei; Zhao, Pinge; Gao, Sande; Liu, Enyi; Rong, Peijing; Yu, Lin (Frontiers in Psychiatry, 2025)
BackgroundMost guidelines on insomnia focus more on the treatment of patients after the onset of the illness, with little elaboration on prevention before the onset of the illness. In particular, treatment of insomnia disorder using TCM preventive treatment is rarely mentioned. Therefore, to improve the rehabilitation and quality of life of patients with insomnia disorder and its high-risk groups, the Affiliated TCM Hospital of Guangzhou Medical University and the Institute of Acupuncture and Moxibustion, CACMS have jointly initiated the compilation of the “Practice guideline for TCM preventive treatment of Insomnia disorder”.MethodsThe guideline will adhere to the principles outlined in WHO Handbook for Guidelines Development, 2nd Edition by the World Health Organization and the Guidelines for the Development of Traditional Chinese Medicine by the Chinese Society of Traditional Chinese Medicine. The quality of evidence and strength of recommendations will be based on the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. The key steps in developing the guideline include: (1) Establishing Guideline Project Group; (2) Conflict of interest management; (3) Research, Selection and Identification of Clinical Questions; (4) Evidence search and evaluation; (5) Quality and grading of evidence; (6) Decision Table for Forming Recommendations; (7) Recommendation Consensus and Determination; (8) Writing the first draft of the guideline; (9) Peer review.DiscussionBased on the theoretical system of “TCM preventive treatment” of Chinese medicine this guideline is to construct a three-tier preventive framework. The development of this guideline can systematically integrate the characteristic techniques of TCM, such as physical identification, emotional regulation, acupuncture and massage, with the evidence-based evidence of modern sleep medicine, and build a new management model.ConclusionThis guideline will serve as an evidence-based reference for standardized TCM preventive treatment methods, promoting the standardization and normative application of TCM preventive treatment in insomnia disorder. Ultimately, this guideline aims to improve the rehabilitation level and life quality of individuals with insomnia disorder and those at high risk of the disease.Clinical trial registrationhttp://www.guidelines-registry.org/,identifierPREPARE-2023CN517.